Molecular Docking Analysis of Human Thymidylate Synthase with the Anticancer Inhibitor Raltitrexed: - Advancing Drug Discovery and Design - Singh, Jagjeet; Soren, Swati; Varshita, Kondakindi; Ambiga, Darshan; Shaurya, Kumar; Samanta, Priyanshu Singh; B Malshetty, Manjunath; Sethi, Kimaya; Singh, Ankita; Kumari, Puja; Jumnani, Prohit; Saini, Anushka (Journal of Neonatal Surgery, 2025)
Molecular docking was employed to elucidate the binding interactions between human thymidylate synthase (hTS) and the clinically established antifolate inhibitor Raltitrexed, with the aim of informing structure based anticancer drug design. The crystal structure of hTS (PDB ID: 1HVY) was prepared by removal of crystallographic water, addition of polar hydrogens, and energy minimization. Raltitrexed’s three dimensional geometry was optimized using MMFF94 force fields. Automated docking was performed using the SwissDock platform, generating multiple binding poses clustered by FullFitness score. The top-ranked pose (Cluster 0) exhibited a binding energy of –53.41 kcal·mol⁻¹ and formed key hydrogen bonds with catalytic residues Cys195 and Arg218, alongside π–π stacking with Phe226 and electrostatic contacts with Glu58 at the active site interface. Secondary clusters (1–3) yielded binding energies in the range of –50.01 to –48.23 kcal·mol⁻¹, corroborating a consistent binding mode. Structural analysis revealed that Raltitrexed occupies the dUMP binding cavity, sterically occluding substrate access and mimicking the native cofactor’s interaction network. Physicochemical and pharmacokinetic assessments indicated favorable lipophilicity (consensus log P = 1.83) and compliance with Lipinski’s Rule of 5, although the high topological polar surface area (TPSA = 180.9 Å²) suggests limited gastrointestinal absorption. Raltitrexed did not inhibit major CYP450 isoforms but was predicted as a P glycoprotein substrate, potentially impacting bioavailability. Overall, docking results validate Raltitrexed’s high affinity and specificity for hTS, reinforcing its mechanism of competitive inhibition. These findings provide atomic level insights into inhibitor enzyme interactions, supporting rational optimization of Raltitrexed analogs with improved pharmacokinetic properties. Future work will involve molecular dynamics simulations to assess the stability of the hTS–Raltitrexed complex under physiological conditions and in vitro enzymatic assays to correlate predicted binding affinities with inhibitory potency.